FACTORS AFFECTING CONSUMER-BASED BRAND EQUITY OF VIETNAMESE PHARMACEUTICAL COMPANIES - Nguyễn Cao Quỳnh Tú; Lưu Tiến Dũng (Tạp chí Khoa học Đại học Đà Lạt)
The concept and importance of a company’s brand have always been widely acknowledged. However, in modern Vietnam, many Vietnamese companies are still unaware of the importance of building their brand. Particularly in the pharmaceutical industry where products are directly related to human health, buying products of famous pharmaceutical brands to help ensure the lowest risk is gradually becoming a habit of consumers. The purpose of this paper is to find out factors affecting consumer-based brand equity of Vietnamese pharmaceutical companies. The study provides a conceptual framework in which brand awareness, brand associations, perceived quality and brand loyalty are related to brand equity. The survey was conducted on a sample of 328 customers at pharmacies and hospitals in Vietnam who have basic knowledge on some of Vietnamese pharmaceutical companies’ brands. The research instruments included an 18-item questionnaire on brand equity, plus demographic questions. Results show that there are four factors affecting the brand equity of Vietnamese pharmaceutical companies, including brand awareness, brand associations, perceived quality, brand loyalty and the correlation between them.